Failure prediction on steel sheet under different loading paths based on fully coupled ductile damage model. (April 2019) - Yue, Z.; Cao, K.; Badreddine, H.; Saanouni, K.; Gao, J.
Highlights: The Lode angle effect is introduced into one fully coupled damage model by one new form. Also this model takes into account the isotropic/kinematic hardenings and the isotropic ductile damage. Various mechanical tests including the uniaxial tensile tests, the pre-notched tensile tests with four notched radii, the butterfly specimen tests under different loading paths, and deep drawing tests are performed to calibrate and validate the proposed model. Through the comparison of numerical and experimental results the wide capabilities of the proposed fully coupled damage model on the prediction of ductile fracture under wide range of loading conditions. Currently, there is less discussion on this aspect with Fully coupled CDM models. Abstract: It is well known that the ductile damage evolution on sheet metal under complex loading conditions is highly dependent on the complexity of the applied loading path. In this study, a fully coupled ductile damage model including the effect of Lode angle and microcracks closure together with the mixed nonlinear isotropic and kinematic hardenings is used to simulate the fracture occurrence of the chosen low carbon steel. Various mechanical tests including the uniaxial tensile tests, the pre-notched tensile tests with four notched radii, the butterfly specimen tests under different loading paths, and deep drawing tests are performed on the chosen low carbon steel sheet to calibrate and validate the proposed model. The influence of the Lode angle on damage evolution is investigated throughout various numerical simulations. These results showed the wide capabilities of the proposed fully coupled damage model on the prediction of ductile fracture under the wide range of loading conditions. Graphical abstract: Image, graphical abstract